2007
DOI: 10.1037/1528-3542.7.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication level and emotional response.

Abstract: We used affective modulation of the eye-blink component of the startle reflex to examine effects of three levels of alcohol intoxication and a no-intoxication control on emotional responses to pleasant, neutral, and unpleasant pictures. Non-problematic student drinkers (n=101; 48 female) were randomly assigned to intoxication groups. Normal inhibition of startle during exposure to pleasant pictures was intact across groups. In contrast, potentiation of startle during viewing of unpleasant pictures was evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 51 publications
1
53
0
2
Order By: Relevance
“…In response to the early studies by Wilson and others, these investigators also used placebo, and in some instances balanced placebo, designs to examine both pharmacological and expectancy effects. Interestingly, when higher doses of alcohol were used than in the original Wilson and Abrams (1977; Abrams & Wilson, 1979) studies, their findings suggested a primarily pharmacological effect on stress response dampening 4 (see also Donohue, Curtin, Patrick, & Lang, 2007). …”
Section: Negative Affect Reliefmentioning
confidence: 95%
See 1 more Smart Citation
“…In response to the early studies by Wilson and others, these investigators also used placebo, and in some instances balanced placebo, designs to examine both pharmacological and expectancy effects. Interestingly, when higher doses of alcohol were used than in the original Wilson and Abrams (1977; Abrams & Wilson, 1979) studies, their findings suggested a primarily pharmacological effect on stress response dampening 4 (see also Donohue, Curtin, Patrick, & Lang, 2007). …”
Section: Negative Affect Reliefmentioning
confidence: 95%
“…With few exceptions (e.g., Donohue, et al, 2007; Ruch, 1993; Stritzke, Patrick, & Lang, 1996; Vuchinich, Tucker, & Sobell, 1979; Weaver, Maslund, Kharazmi, & Zillman, 1985), there has been little investigation of the impact of alcohol on responses to positive stimuli. Positive responding may be especially important to study in a social context, and my colleagues and I are currently completing analyses on a group study that includes a comedy routine manipulation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Specifically, the authors proposed that alcohol consumption results in a narrowing of perception, such that the drinker’s attention becomes focused on the most salient factors in the environment, and, depending on the nature of those factors, the drinker’s thoughts and actions can be influenced in various ways. However, as levels of intoxication increase beyond what is typically considered “moderate” levels of consumption, the contextual influences appear to wane with the direct effects of alcohol becoming more unconditional, at least with respect to emotional response (Donohue et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Se ha postulado que la modulación afectiva de la RS podría identificar a aquellos sujetos con dependencia de alcohol que tendrían más riesgo de sufrir una recaída en el consumo de alcohol, de modo que éstos serían aquéllos que basalmente reaccionan con una menor RS ante la presentación de estímulos relacionados con el alcohol (Koenecke, Jiménez-Gimé-nez, Borrell y Loeber et al, 2007). Por otro lado, la modulación afectiva de la RS se ha utilizado para demostrar que los sujetos no intoxicados o con un grado leve de intoxicación presentan una potenciación de la RS durante la presentación de imágenes aversivas, en comparación con los sujetos con intoxicaciones moderadas o severas, lo que hablaría a favor de un efecto ansiolítico del alcohol (Donohue, Curtin, Patrick y Lang, 2007). included 40 alcohol dependent men, who proceeded from study 2, and who were assessed with laboratory impulsivity paradigms after having been tested on SR and PPI.…”
Section: Modulación Afectiva De La Rs a Través De La Presentación De unclassified